The properties of ceramic materials as artificial substrate for coral rehabilitation and restoration - Ramli, Rafindde; Abd. Kadir, Nor Azmah; Saad, Shahbudin; Ariffin, Mohd Yusoff (2013)
Artificial substrate made from ceramic are a non-toxic, pH neutral, and eco-safe material that is ideal for the settlement of corals and other invertebrates. Unlike artificial substrate made from concrete, metal or other discarded materials, ceramic materials delivers many of the biological, ecological and physical conditions necessary for normal reef ecosystem function. The substrate was made from customized ceramic formulation in a shape a fish bone using slip casting technique and fired at several temperatures. The fired bodies were analysed in order to determine physical and chemical properties in order to select suitable properties to be used as artificial coral substrate. The selected artificial substrate was installed at field test site at Pasir Akar, Pulau Redang Marine Park, Terengganu and monitored within specific interval duration in order to observe its suitability and effectiveness for coral growth. Identification of coral species and algae growing on the artificial coral substrate was done in order to find out the growth selectivity of coral species on the artificial ceramic substrate.